2001
DOI: 10.1109/12.910816
|View full text |Cite
|
Sign up to set email alerts
|

Inherently lower-power high-performance superscalar architectures

Abstract: Victor V. Zyuban When it comes to performance, modern computer design has become a well structured art which starts with instruction sets that maximize opportunities for concurrency, follows through with fast organizational techniques such as pipelining and super scalar execution, and ends with clever macro and circuit designs that are based on inherently fast CMOS fabrication technologies. When it comes to low power, however, exactly the opposite is true. Current techniques start with lowering supply voltages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 106 publications
4
127
0
Order By: Relevance
“…Since we are concerned with differences among alternative schedulers, we prefer not to include the effect of cycle time in our metric, to isolate the effect of the schedulers. A study of the impact of clustering on cycle time can be found elsewhere [ 191 as well as on energy consumption [26], which is another important factor that can be reduced through clustering.…”
Section: Performance Resultsmentioning
confidence: 99%
“…Since we are concerned with differences among alternative schedulers, we prefer not to include the effect of cycle time in our metric, to isolate the effect of the schedulers. A study of the impact of clustering on cycle time can be found elsewhere [ 191 as well as on energy consumption [26], which is another important factor that can be reduced through clustering.…”
Section: Performance Resultsmentioning
confidence: 99%
“…In high performance processors research work can be found that is devoted to defining mechanisms that decrease the energy of multiported register files. Regarding the hardware approaches to the problem, Zyuban and Kogge (1998) have studied the complexity of shared register files and Seznec et al (2002) and Zyuban and Kogge (2001) have proposed distributed schemes and techniques to split the global microarchitecture into distributed clusters with subsets of the register file and functional units. Similarly, trying to reduce the complexity of the register files, Cruz et al (2000) have studied the benefits of multilevel register file organisations.…”
Section: Related Workmentioning
confidence: 99%
“…In high-performance processors research devoted to defining mechanisms that decrease the energy of multiported register files can be found. Regarding the hardware approaches to the problem, Zyuban and Kogge [31] have studied the complexity of shared register files and Scznec et al [32] and Zyuban and Kogge [33] have proposed distributed schemes and techniques to split the global microarchitecture into distributed clusters with subsets of the register file and functional units. Similarly, other works like [34] have studied the benefits of multilevel register file organizations.…”
Section: Related Workmentioning
confidence: 99%